Metformin reduces urate nephropathy in experimental nephrolithiasis - V. Y. Perfil’ev (Regulatory Mechanisms in Biosystems, 2017)
The objective of the article is to evaluate the effectiveness of metformin in the prevention and treatment of experimental urate nephropathy. About 33% of the populations of developed countries suffers from metabolic syndrome. The relationship between metabolic syndrome, especially insulin resistance, with gout and urate nephrolithiasis, is now proven. The search for a common pathophysiological link in the development of these conditions allows us to identify insulin-dependent excessive urinary acidification due to impaired education and renal ammonium transport. We suggested the use of drugs that can increase the sensitivity of tissues to insulin, and induce a decrease in the manifestations of urate nephropathy. The study was performed on 30 male Wistar rats weighing 250–300 g. For the induction of urate nephropathy in rats, we used the classical model of inhibition of uricase by oxononium acid. Metformin was administered at a dose of 150 mg/kg in the treatment and prophylactic regimens. It was found that the use of metformin both in prophylactic and therapeutic regimen leads to a reliable decrease the level of uric acid in blood plasma and urine in rats with experimental urate nephrolithiasis. We found that the preventive use of metformin brought significant relief after experimental urate nephropathy, as evidenced by a shift in urine pH to the alkaline side, a decreased lactate dehydrogenase activity in urine, as well as a decrease in the processes of free radical oxidation in the blood and in the kidneys of the animals.